Helicopter parenting and college student depression: the mediating effect of physical self-esteem - Wang, Chaolian; Shi, Heng; Li, Geng (Frontiers in Psychiatry, 2024)
Background: Depression is one of the most common and prevalent mental disorders, and college students are a high-risk group for depression. Helicopter parenting plays an important role in depression, but the mechanism is still ambiguous. Therefore, this study investigates the specific impact and mechanism of helicopter parenting on college students' depression.Methods: Employing a questionnaire-based approach, we assessed the relationship between helicopter parenting, Physical self-esteem, and depression. The questionnaire comprised three scales: the Helicopter Parenting Scale, Physical Self-Esteem Scale, and Self-Rating Depression Scale. The study sample included 539 university (average age 18.84 ± 1.1 years; 184 males and 355 females).Results: Helicopter parenting demonstrated significant negative predict with physical self-esteem (β= -.75, p ＜ .001), and positive predict depression (β =.33, p ＜ .001). Helicopter parenting impacts depression among college students through two channels: solely via physical self-esteem (mediating effect value: .66), and through direct influence (effect value: .64).The insights from this study address the two pivotal questions about "why" and "how" helicopter parenting influences depression in college students, offering recommendations for managing depressive moods among college students.